2021
DOI: 10.3390/jof7030209
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone Networks in Fungal Pathogens of Humans

Abstract: The heat shock proteins (HSPs) function as chaperones to facilitate proper folding and modification of proteins and are of particular importance when organisms are subjected to unfavourable conditions. The human fungal pathogens are subjected to such conditions within the context of infection as they are exposed to human body temperature as well as the host immune response. Herein, the roles of the major classes of HSPs are briefly reviewed and their known contributions in human fungal pathogens are described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 122 publications
0
14
0
Order By: Relevance
“…From this table, we decided to work with the chaperonin GroEL-like protein, also known as heat shock protein 60 (Hsp60), because it was reported to be involved in the pathogen-host interaction in other fungal species and we obtained the highest sequence coverage (48.9%) and Andromeda score (323) for this protein. The protein was isolated from both prokaryotic and eukaryotic cells, and in the latter, the canonical function is performed in the mitochondria, assisting the folding of proteins with regions of exposed hydrophobic β-sheets and molecular weight lower than 60 kDa [65]. However, it was also reported as a moonlighting protein found in the cell wall of H. capsulatum and P. brasiliensis.…”
Section: Polypeptide Composition Of Peptidorhamnomannanmentioning
confidence: 99%
“…From this table, we decided to work with the chaperonin GroEL-like protein, also known as heat shock protein 60 (Hsp60), because it was reported to be involved in the pathogen-host interaction in other fungal species and we obtained the highest sequence coverage (48.9%) and Andromeda score (323) for this protein. The protein was isolated from both prokaryotic and eukaryotic cells, and in the latter, the canonical function is performed in the mitochondria, assisting the folding of proteins with regions of exposed hydrophobic β-sheets and molecular weight lower than 60 kDa [65]. However, it was also reported as a moonlighting protein found in the cell wall of H. capsulatum and P. brasiliensis.…”
Section: Polypeptide Composition Of Peptidorhamnomannanmentioning
confidence: 99%
“…Intriguingly, in fungal pathogens, Cdc42p and other Rho GTPases contribute to many fungal attributes underlying virulence (Brand et al, 2014;Chen et al, 2019;Silva et al, 2019). Intriguingly, HSPs have also been implicated in the regulation of fungal pathogenesis (Horianopoulos and Kronstad, 2021). It will be interesting to explore whether HSPs regulate Rho GTPase levels to control aspect of the pathogenic response.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp12 is one of several small heat shock proteins, which often act as holdases, i.e., they have a high affinity for denatured proteins, whom they immobilize until Hsp70 and its co-chaperones reactivate them in an ATP-dependent fashion [ 149 , 150 ]. Data from other fungal species (particularly S. cerevisiae ) indicate that Hsp12 is involved in response to a variety of stress sources, in modulating the physical properties of the cell wall, as well as in resistance to certain antifungals, for instance, amphotericin B [ 150 ]. As mentioned above, data from CrzA null mutants of A. fumigatus indicated that the Hsp12 Scf1 homolog (Afu1g17370) could be a target for antifungal development.…”
Section: Other Hsp Proteinsmentioning
confidence: 99%